The effect of UV degradation on the recovery behavior of cut-pile carpets after static loading. Issue 2 (1st February 2017) - Jafari, Sahar; Ghane, Mohammad; Moezzi, Meysam
Abstract: UV exposure is a major source of degradation and deterioration of textile materials including carpets. Samples of machine-woven cut-pile carpets were prepared and exposed to different UV exposure times using a UV chamber. The short-term static loading was then applied to the carpets and the recovery properties and the thickness loss of the samples were measured using standard methods. The results showed that the variation of the thickness loss in different load removal times was steep at first and obeyed an exponential trend. As the time was increased, it tended to a lower slope and at a certain point, it reached a constant value. No statistically significance difference was observed in the thickness losses following 60 min of load removal time after static loading. UV radiation caused a significant increase in the thickness loss, or compression of piles, under static loading. Curve fitting process was applied and then the theoretical recovery speed equation was predicted. The results revealed that the compression of the carpets under static loading was higher in the case of UV exposure carpets. However, the speed of the recovery after load removal was much higher in the case of UV exposure carpets, in comparison to the non-exposure carpets.